Downregulation of PRDM1 promotes cellular invasion and lung cancer metastasis - Zhiyan Zhu; Hao Wang; Yiliang Wei; Fanrong Meng; Zhe Liu; Zhenfa Zhang (Tumor Biology)
The zinc-finger transcription factor PRDM1 (PR domain containing 1) plays key roles in the development of malignant lymphoma, leukaemia and some non-haematopoietic cancers, including breast cancer, colorectal cancer and glioma. However, little is known regarding the function of PRDM1 in the progression of lung cancer. Here, we found that PRDM1 is expressed in normal human lung epithelium but is downregulated in lung cancer cells. Decreased expression of PRDM1 correlates with poor prognosis in lung cancer. Depletion of PRDM1 in lung cancer cells promotes cellular invasion and anoikis resistance in vitro and lung metastasis in vivo. PRDM1 is silenced by an ectopically expressed lymphocyte-specific transcription factor Aiolos. The transcription of these two genes is negatively correlated in 206 lung epithelial cell lines. Our results indicate that PRDM1 functions as a tumour suppressor in lung cancer.